Test of CP invariance in Z → μ+μ-γ decay - Dova, María Teresa (1998)
We report on the first test of CP invariance in Z decays with hard photon radiation. The data recorded with the L3 detector at centre-of-mass energies near the Z resonance are used to search for CP violation in the reaction e+e-→ μ+μ-γ. No evidence for CP violation is found and limits on the CP-violating form factors fμA and fμV are derived.